Perception of the filmed urban space: an analysis of the imaginaries of Madrid constructed through series and social networks - Diego Antonio Barrado-Timon; Carmen Hidalgo-Giralt; Antonio Palacios-García; Héctor Ochoa-Ortiz; Miguel Sevilla-Callejo (Boletín de la Asociación de Geógrafos Españoles)
Concurrent with the expansion of visual culture, film tourism has experienced a significant boost in recent decades, and the motivation to visit places where series made for television or similar platforms were filmed has been added to this modality. In this context, and taking the city of Madrid as a reference, this work proposes a line of research wherein analysis of the relationships between geographical and audiovisual spaces through cultural and tourist use unites the representation of both, by way of social networks (specifically, Twitter). As regards methodology, an ‘application programming interface’ has been designed which permits the download of a sample of tweets useful for both quantitative and qualitative analysis. The main results indicate the impacts that fiction series have had on recognition of the city (or certain of its elements) as well as relationships established between the narrative and geographical spaces when the latter are referenced via on-site activities. Theoretically, this research focuses on the relationship between real geographies, imagined geographies, and simulacra, as well as their involvement in the commodification of space and in the construction of vicarious geographical experiences.